(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The project objective of the Community Based Rural Infrastructure Project is to reduce rural poverty in up to 600 of the poorest rural communes (a commune in Vietnam is the lowest administrative unit comprising several villages and is inhabited by some 3,600 people, on average) in 13 provinces in Central Vietnam. There are three project components. The first strengthens decentralized planning and implementation capacity by providing training for government and project staff as well as community facilitators; and supporting information campaigns to ensure widespread public understanding, transparency and accountability, including distribution of printed materials, signboards, newsletters, and broadcasts by mass media. The second component provides grants to communes for infrastructure development within communes and infrastructure works that impact two or more communes. The third component finances the operating expenses of a central project management unit.
Keywords: Community development,Phát triển cộng đồng,Rural development,Phát triển nông thôn; Vietnam,Việt Nam,Vietnam,Việt Nam